RESPONS TIDAK LINIER CAMPURAN AC-WC PG70 ELASTOMER DENGAN ANTI-STRIPPING AGENT TERHADAP PENUAAN DAN KELEMBAPAN - irwan nasihin; Aine Kusumawati; Russ Bona Frazila (Direktorat Bina Teknik Jalan dan Jembatan, 2026)
Moisture and aging can alter asphalt mixture performance through various mechanisms, including retention of tensile strength, permanent deformation, and mass loss. However, the effectiveness of the anti-stripping agent in Performance Grade 70 (PG70) elastomer-modified Asphalt Concrete-Wearing Course (AC-WC) mixtures can be difficult to interpret when assessed using a single performance parameter. This study presents a multi-parameter evaluation of the nonlinear response of PG70 elastomer-modified AC-WC mixtures with an anti-stripping agent under unaged, short-term aging, and long-term aging conditions. The optimum asphalt content was determined using Marshall and volumetric analysis, while the optimum anti-stripping agent (ASA) content was selected based on the Marshall Immersion test. Mixture-level performance was evaluated using Indirect Tensile Strength Ratio/Tensile Strength Ratio (ITS/TSR), the Hamburg Wheel Tracking Device (HWTD), and the Cantabro Loss Test, while Dynamic Shear Rheometer (DSR) testing was used as supporting binder-level analysis. The results show that 0.3% ASA produced the highest retained Marshall stability and was selected as the optimum content. At this dosage, the mixtures exhibited higher TSR, lower final rut depth, and lower Cantabro Loss than the control mixture across all aging conditions. Short-term aging improved rutting resistance but produced the lowest TSR and the highest Cantabro Loss. Long-term aging increased rutting susceptibility in the control mixture, whereas the mixture with the anti-stripping agent maintained a more stable response. DSR results indicate that binder-level rheological changes did not fully represent mixture-level performance. These findings suggest that the effectiveness of the anti-stripping agent in PG70 elastomer-modified AC-WC mixtures under aging and moisture exposure should be assessed through a multi-parameter evaluation framework. Kata Kunci: AC-WC PG70 elastomer, anti-stripping agent, penuaan, kelembapan, evaluasi multi-parameter. Keywords: PG70 elastomer AC-WC, anti-stripping agent, aging, moisture, multi-parameter evaluation